The Impact of Students’ Learning Interest on Students’ Process Skill in Mathematics - Syaiful, Syaiful; Kamid, Kamid; Kurniawan, Dwi Agus; Rivani, Putri Ayu (Journal of Education Reseach and Evaluation, 2021)
The success of education in a country automatically also shows the progress of a country. In essence, education itself is a conscious effort to develop personality and within oneself. School is a place where education is held for the purpose of national education. However, not all schools can achieve the expected goals. Like a school that has priority on certain subjects. One of them is Madrasah Tsanawiyah which dominates subjects with religion. So the importance of this study aims to determine the differences and the relationship between the interests and skills of students in learning mathematics with flat side space material. This study uses quantitative methods with associative and comparative types. The sampling technique used in this study used simple random sampling. From the results of the T test and the correlation obtained, it was found that there were differences in the process skills and interests of students with regard to the material build flat side space. This is evidenced by the value of sig (2-tailed) 0.000 < 0.05. So can be concluded that student interest affects the process skills of students at MTsN (Madrasah Tsanawiyah) and there is a significant relationship between students' interest and process skills in mathematics with flat-sided geometry. There are limitations in this study where this study only measures students' skills, interests have not been tested with other variables such as attitudes, motivation and others.